Analisa Proksimat Ekstrak Limbah Kulit Kedua Bawang Merah (Allium Cepa L.) - Zul Muzhahir; Yan El Rizal Unzilatirrizqi; Melly Fera (Journal of Food and Agricultural Product, 2023)
This research used samples of shallot skin (Allium cepa L.) where shallot skin contains many chemical compounds such as flavonoids, saponins, tannins, glycosides, and steroids or triterpenoids. The aim of this research was to determine the amount of proximate levels in the waste extract of the second skin of shallots and the process of preserving duck meat using shallot skin waste. The methods used in this research are protein testing using the Kjedhal method, fat content using the Soxhlet method, water content using the oven method, ash content using the tannur method, and carbohydrates using the by different method. The results of the proximate test on the waste extract of the second skin of shallots, namely water content amounting to 98.34% ash content 0.12% fat content 0.03% protein content 0.24% and carbohydrates amounting to 1.28%. Keywords: Proximate, Shallots, Shallot skin